NGOs and their Impact on the Preservation of Peace and Security in International Relations - Stefan, Gheorghe (Journal of Danubian Studies and Research, 2023)
The international non-governmental organization is an organizational structure that appears due to private or mixed initiatives, being outside any intergovernmental agreement and bringing together people from various social categories, private or public institutions, non-governmental organizations (NGOs) belong to a field that finds in the sphere of the civil society and have as objects, provided in the statute, the identification of some solutions to the problems of the society, thus encouraging a democratic and authentic society. They are independent of the state, and what makes them special in relation to other organizations is the non-profit character, based on the benefit of the public and not the private one.